Interactions of Hydrophilic Plasticizer Molecules with Amorphous Starch Biopolymer—An Investigation into the Glass Transition and the Water Activity Behavior - Liu, Huihua; Chaudhary, Deeptangshu; Ingram, Gordon; John, Joseph (John Wiley & Sons, Inc., 2011)
In this article, we demonstrated that within a hydrophilic biopolymer–plasticizer system, the molecular ‘‘activity’’ of the plasticizer also influenced the extent of these interactions. We demonstrated through an analysis of crystallinity and calorimetry results that the equilibrium moisture content within the starch matrix can preferentially interact with the hydrophilic plasticizers and modify the polymer recrystallization process to an extent that the commonly acknowledged relationship between the crystallinity and the glass transition behavior is disrupted. Two plasticizers, glycerol (three AOH groups) and xylitol (five AOH groups), were selected. The water sorption isotherm of polymer samples with 5–20 wt % (dry basis) plasticizers were examined across a water activity range from ~0.11 to ~0.95 and using Guggenheim-Anderson-de Boer analysis, we compared the molar sorption enthalpies of various starch–plasticizer mixtures. Finally, the competitive plasticization between water and plasticizer molecules at different water activities was also discussed using known glass transition models. The analyses validated the antiplasticization limit for glycerol to be ~10–15 wt %, but for xylitol, its anti-plasticization behavior did not manifest till 20 wt %.